2006
DOI: 10.1534/genetics.106.063891
|View full text |Cite
|
Sign up to set email alerts
|

Double-Strand Break Repair in Bacteriophage T4: Recombination Effects of 3′–5′ Exonuclease Mutations

Abstract: The role of 39-59 exonucleases in double-strand break (DSB)-promoted recombination was studied in crosses of bacteriophage T4, in which DSBs were induced site specifically within the rIIB gene by SegC endonuclease in the DNA of only one of the parents. Frequency of rII 1 recombinants was measured in two-factor crosses of the type i 3 ets1, where ets1 designates an insertion in the rIIB gene carrying the cleavage site for SegC and i's are rIIB or rIIA point mutations located at various distances (12-2040 bp) fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Thus, the marker that is 15 bp from the insertion is actually 68 bp from the 39 end of the broken DNA molecule. Regarding the resection events on the broken DNA, Shcherbakov et al (2006a) showed that the T4 exonuclease DexA contributes to erosion of DNA only very near a break and that the T4 DNA polymerase proofreading exonuclease contributes to erosion of DNA both near and farther from a break (both tested in an MR-proficient infection). The simplest model to explain our results is that the reduced amount of MR complex in the suppressed triple amber mutant allows increased access to DexA exonuclease (given the strong effect that we see with the nearby marker FC11) and perhaps also to the T4 DNA polymerase exonuclease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the marker that is 15 bp from the insertion is actually 68 bp from the 39 end of the broken DNA molecule. Regarding the resection events on the broken DNA, Shcherbakov et al (2006a) showed that the T4 exonuclease DexA contributes to erosion of DNA only very near a break and that the T4 DNA polymerase proofreading exonuclease contributes to erosion of DNA both near and farther from a break (both tested in an MR-proficient infection). The simplest model to explain our results is that the reduced amount of MR complex in the suppressed triple amber mutant allows increased access to DexA exonuclease (given the strong effect that we see with the nearby marker FC11) and perhaps also to the T4 DNA polymerase exonuclease.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study of 46 + infections, we found that the co-conversion frequency is very high near the break but drops off as a function of distance from the DSB (Stohr and Kreuzer 2002). We argued that exonuclease action starting at the break usually destroys the wild-type sequence on the cut chromosome when the flanking marker is very close to the break, but that the exonuclease action decreases stochastically with distance from the break (Stohr and Kreuzer 2002; also see Shcherbakov et al 2006a).…”
Section: Recombination Of Linked Markers During Dsb Repair With Limitmentioning
confidence: 99%